Studies on characterization of nano CaCO3 prepared by the in situ deposition technique and its application in PP-nano CaCO3 composites - Mishra, Satyendra; Sonawane, S. H.; Singh, R. P. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The elegant approach of in situ deposition technique was used for the synthesis of nano CaCO3 the nanosize of particles was confirmed by the X-ray diffraction (XRD) technique. Differential scanning calorimetry (DSC) was used for determination of the enthalpy. The nano CaCO3 polypropylene (PP) composites were prepared by taking 2 and 10 wt % of different nanosizes (21-39 nm) of CaCO3. Conversion of the alpha phase to beta was observed in the case of 2 wt % of a 30-nm sized amount of CaCO3 in a PP composite. The decrement in DeltaH and percent. crystallinity, as well as the increment in melt temperature were recorded for 6 wt % nano CaCO3 with a decrease in nanosize from 39 to 21 nm. The increment in tensile strength with an increase in the amount of nano CaCO3 was observed, and the tower particle size shoved Greater improvement. The improvement in thermal and mechanical properties is because of the formation of a greater number of small spherulites uniformly present in the PP matrix. (C) 2004 Wiley Periodicals, Inc.
Keywords: Crystallization; DSC; mechanical and thermal properties; nano CaCO3; polypropylene; XRD

Ultrasound assisted synthesis of polyacrylic acid-nanoclay nanocomposite and its application in sonosorption studies of malachite green dye - Sonawane, S. H.; Chaudhari, P. L.; Ghodke, S. A.; Parande, M. G.; Bhandari, Vinay M.; Mishra, Satyendra; Kulkarni, R. D. (Ultrasonics Sonochemistry, 2009)
Synthesis of nanoclay nanocomposite has been undertaken by using polyacryalic acid (PAA) in aqueous medium and ultrasound environment and its application in dye removal has been investigated. The synthesized product was characterized by using FTIR and XRD techniques. The sonosorption capacity of the product namely PAA-nanoclay composite was determined by choosing malachite green (MG) dye as a model pollutant. The effects of various parameters such as nanocomposite loading, pH, various process conditions etc. have been studied. On comparing the results obtained with that of nanoclay as an adsorbent, it was found for an initial concentration of 500 mg/l, the PAA-nanoclay nanocomposite exhibited higher percentage of pollutant removal (68%) and for nanoclay it was 54%. The adsorption data has been correlated using Langmuir and Freundlich models. The fit of the Freundlich isotherm model was found to be good in the entire range of concentration for the experimental sorption data obtained on the nanoclay nanocomposite. A plausible reaction mechanism for use of PAA-nanoclay nanocomposite as ail adsorbent is also proposed. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Malachite Green; Nanocomposite; Polyacrylic acid; Sonosorption; Ultrasound

Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound

Intensification of extraction of curcumin from Curcuma amada using ultrasound assisted approach: Effect of different operating parameters - Shirsath, S. R.; Sable, S. S.; Gaikwad, S. G.; Sonawane, S. H.; Saini, D. R.; Gogate, P. R. (Ultrasonic Sonochemistry, 2017)
Curcumin, a dietary phytochemical, has been extracted from rhizomes of Curcuma amada using ultrasound assisted extraction (UAE) and the results compared with the conventional extraction approach to establish the process intensification benefits. The effect of operating parameters such as type of solvent, extraction time, extraction temperature, solid to solvent ratio, particle size and ultrasonic power on the extraction yield have been investigated in details for the approach UAE. The maximum extraction yield as 72% was obtained in 1 h under optimized conditions of 35 degrees C temperature, solid to solvent ratio of 1:25, particle size of 0.09 mm, ultrasonic power of 250 W and ultrasound frequency of 22 kHz with ethanol as the solvent. The obtained yield was significantly higher as compared to the batch extraction where only about 62% yield was achieved in 8 h of treatment. Peleg's model was used to describe the kinetics of UAE and the model showed a good agreement with the experimental results. Overall, ultrasound has been established to be a green process for extraction of curcumin with benefits of reduction in time as compared to batch extraction and the operating temperature as compared to Soxhlet extraction.
Keywords: Acrylamide; Cavitation; Curcumin Extraction; Design; Enhancement; Functionalized Silica; kinetics; Microwave; Nanoparticles; Natural-products; Optimization; Phenolic-compounds; Process Intensification; Solid-liquid Extraction; Ultrasound